Limitations of specific coagulation tests for direct oral anticoagulants: a critical a nalysis - Ebner, Matthias; Rupp, André (Journal of the American Heart Association, 2018)
BackgroundDuring treatment with direct oral anticoagulants (DOAC), coagulation assessment is required before thrombolysis, surgery, and if anticoagulation reversal is evaluated. Limited data support the accuracy of DOAC‐specific coagulation assays around the current safe‐for‐treatment threshold of 30 ng/mL.Methods and ResultsIn 481 samples obtained from 96 patients enrolled at a single center, DOAC concentrations were measured using Hemoclot direct thrombin inhibitor assay, Biophen direct thrombin inhibitor assay or ecarin clotting time for dabigatran, chromogenic anti‐Xa assay (AXA) for factor Xa inhibitors (rivaroxaban, apixaban) and ultraperformance liquid chromatography-tandem mass spectrometry as reference. All dabigatran‐specific assays had high sensitivity to concentrations >30 ng/mL, but specificity was lower for Hemoclot direct thrombin inhibitor assay (78.2%) than for Biophen direct thrombin inhibitor assay (98.9%) and ecarin clotting time (94.6%). AXA provided high sensitivity and specificity for rivaroxaban, but low sensitivity for apixaban (73.8%; concentrations up to 82 ng/mL were misclassified as <30 ng/mL). If no DOAC‐specific calibration for AXA is available, results 2‐fold above the upper limit of normal indicate relevant rivaroxaban concentrations. For apixaban, all elevated results should raise suspicion of relevant anticoagulation.ConclusionsDOAC‐specific tests differ considerably in diagnostic performance for concentrations close to the currently accepted safe‐for‐treatment threshold. Compared with Biophen direct thrombin inhibitor assay and ecarin clotting time, limited specificity of Hemoclot direct thrombin inhibitor assay poses a high risk of unnecessary anticoagulation reversal or treatment delays in patients on dabigatran. While AXA accurately detected rivaroxaban, the impact of low apixaban levels on the assay was weak. Hence, AXA results need to be interpreted with extreme caution when used to assess hemostatic function in patients on apixaban.Clinical Trial RegistrationURL: https://www.clinicaltrials.gov. Unique identifiers: NCT02371044, NCT02371070.